Pengaruh Perubahan Harga Emas, Tingkat Suku Bunga dan Nilai Tukar Terhadap Return Saham IHSG - Indra Wijaya; Romi Ferdian; Amalia; Siti Aisyah; Rumintar J. H. Marpaung (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze and determine the effect of changes in gold prices, interest rates and exchange rates on IHSG stock returns. The type of research used in this study is quantitative research, testing theories through measuring research variables with numbers and analyzing data with statistics. The object of research can be an object, thing, or person that can provide data or information needed for research. The objects in this study are data on changes in gold prices, interest rates and exchange rates and the Composite Stock Price Index (IHSG) in 2021-2024. The results of this study found that changes in gold prices, interest rates, and exchange rates all have a significant effect on IHSG stock returns (Composite Stock Price Index). These three factors often interact and influence each other, both directly and indirectly, in determining the performance of the stock market in Indonesia.